Rational fabrication of a new ionic imprinted carboxymethyl chitosan-based sponge for efficient selective adsorption of Gd(iii). Issue 5 (24th January 2022) - Liu, Enli; Shi, Junyou; Lin, Xue; Xu, Wenbiao; Feng, Liyun; Hong, Yuanzhi
Abstract : In this work, a new PEI-CMC-IIS adsorbent with 3D network structure was fabricated for the selective adsorption of Gd(iii ). Abstract : The selective recovery of Gd(iii ) from wastewater is very meaningful for the prospective development of economics and the environment. To overcome disadvantages of poor adsorption capacity, low selectivity and complex preparation process in conventional adsorbents, herein a new ionic imprinted carboxymethyl chitosan (CMC) sponge functionalized by hyperbranched polyethyleneimine (PEI) with a 3D network structure (PEI-CMC-IIS) was successfully prepared and applied in the selective adsorption of Gd(iii ). The PEI-CMC-IIS is endowed with lots of amino groups due to the combination of biomass CMC with highly branched PEI, which is helpful for the adsorption of Gd(iii ). The imprinting sites are located at the surface of channels in PEI-CMC-IIS, which can achieve the adsorption specificity to Gd(iii ) and improve adsorption capacity. It is found that the maximum adsorption capacity of PEI-CMC-IIS is 38.64 mg g −1 at pH = 7. Meanwhile, the selectivity tests suggest that the PEI-CMC-IIS presents preferential adsorption for Gd(iii ) with a distribution coefficient of 437.5 mL g −1 . Furthermore, the PEI-CMC-IIS displays excellent reusing and regeneration ability. Our findings will bring about potential application in fabrication of other high-efficiency adsorbents for selective adsorption of Gd(iii ).